1997
DOI: 10.1046/j.1365-2281.1997.01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characteristics and hormonal profile of young normotensive men with exaggerated blood pressure response to exercise

Abstract: Exaggerated blood pressure (BP) response to exercise in normotensive subjects is considered as a predictor of future hypertension. The aim of the study was to find out whether elevated BP response to exercise is associated with any other haemodynamic, metabolic or hormonal abnormalities. Abnormal BP response to exercise, i.e. systolic BP (SBP) > 200 mmHg at 150 W or lower workload, was found in 37 out of 180 normotensive, male students, aged 20-24 years. Fifteen students with elevated exercise BP (group E) vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
5
14
0
Order By: Relevance
“…Fitness level and ambulatory systolic BP were associated with EXBPR to exercise in line with previous studies, [25][26][27] whereas resting BP was Abbreviations: bpm, beats per minute; EXBPR, exaggerated blood pressure response; HR, heart rate; recovery DBP (3 minutes), diastolic blood pressure at the end of the third minute of recovery; recovery HR, heart rate at the end of the third minute of recovery; recovery SBP (3 minutes), systolic blood pressure at the end of the third minute of recovery; stage 2 SBP, systolic blood pressure during the second stage of exercise. Values are mean AE standard deviation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Fitness level and ambulatory systolic BP were associated with EXBPR to exercise in line with previous studies, [25][26][27] whereas resting BP was Abbreviations: bpm, beats per minute; EXBPR, exaggerated blood pressure response; HR, heart rate; recovery DBP (3 minutes), diastolic blood pressure at the end of the third minute of recovery; recovery HR, heart rate at the end of the third minute of recovery; recovery SBP (3 minutes), systolic blood pressure at the end of the third minute of recovery; stage 2 SBP, systolic blood pressure during the second stage of exercise. Values are mean AE standard deviation.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast with our results, a previous study found that the EXBPR to exercise was not associated with impaired glucose metabolism in 28 nonsmoking healthy male students, a finding possibly explained by the differences in exercise testing methodology and clinical characteristics with respect to our study. 25 We preliminarily excluded patients with increased LVMI to warrant associations not complicated by established left ventricular hypertrophy, a known positive correlate of EXBPR to exercise. 26 Finally, in our study, the association between age and EXBPR to exercise faded away in the multivariable analysis because (1) we implemented sex-and age-adjusted criteria to define the exercise BP response and (2) we preliminary excluded patients unable to reach the second stage of the standardized test as well as patients 60 years and older.…”
Section: Discussionmentioning
confidence: 99%
“…The SAP mean as well as SPL in wakefulness and SPL in 24 hours were significantly higher in the HR group, although within the reference range, confirming the findings by Nazar et al 23 , who observed an association between SAP at stress with the 24-hour mean and SAP during wakefulness. These results reinforce the hypothesis of a sympathetic hyperreactivity in HR individuals 4 , corroborated by the elevation of the diurnal parameters and their normality during sleep.…”
Section: Discussionsupporting
confidence: 89%
“…In this subgroup, ExBPR is not useful to identify masked hypertension. However, it is still possible that in young patients with low BP levels, ExBPR is associated with masked hypertension, as has been previously described . In our population, we could not identify risk factors for masked hypertension.…”
Section: Discussionmentioning
confidence: 61%